The role of Islamic education teacher in developing CERIA concept for students - Nor Munfarida (ATTARBIYAH: Journal of Islamic Culture and Education, 2017)
AbstractMAN Suruh Semarang Regency has CERIA vision (smart, energetic, religious, scientific, practice). This research wants to know the role of Islamic education’s teacher in developing Ceria concept and how the Ceria concept implemented by the students. This research used qualitative approach. There are three technique in collecting data. They are: observation, documentation, and interview. The researcher as instrument take data by in-depth interview. There are three steps in analyzing data: data reduction, display data, and data verification. The respondent who become the source of information are the headmaster, Islamic education’s teacher, guidance and counseling’s teacher, and students. Based on the observation which lasted for two months, the researcher can conclude: 1) teacher plays an important role in creating CERIA concept. Teacher as an initiator, class manager, motivator, facilitator, and evaluator; 2) “Ceria” concept implementation by the students of MAN Suruh in the form of madrasah policy which encourage the comfortable and conducive environment for the students learning. Various academic and non-academic to develop students’ potential. The growth of main character to create the harmony of the students’ friendship. Keyword: the role of Islamic education teacher, CERIA (smart, energetic, religious, scientific, practice), concept implementation AbstrakMAN Suruh Kabupaten Semarang mempunyai visi CERIA (Cerdas, Energik, Religius, Ilmiah, Amaliyah). Penelitian ini bertujuan untuk mengetahui peran guru PAI dalam menunmbuhkembangkan konsep Ceria dan mengetahui bagaimana implementasi konsep CERIA pada peserta didik. Penelitian ini menggunakan pendekatan kualitatif. Teknik pengumpulan data ada tiga metode utama yang dipakai yaitu, observasi, dokumentasi, dan wawancara. Peneliti mengambil peran sebagai instrumen untuk menggali data yang lebih lengkap melalui indepth interview. Adapun analisis data melalui tiga tahapan yaitu: reduksi data, penyajian data (display), dan verifikasi. Sebagai responden yang menjadi sumber informasi adalah kepala madrasah, guru PAI, guru BK, dan siswa. Berdasarkan penelitian yang berlangsung selama dua bulan dapat disimpulkan hasil penelitian sebagai berikut: 1) Guru mengambil peran sangat positif dalam mewujudkan konsep CERIA. Peran guru sebagai inisiator, pengelola kelas, motivator, fasilitator, dan evaluator; (2) Implementasi konsep Ceria pada peserta didik di MAN Suruh dalam wujud kebijakan madrasah yang mendukung dalam pembentukan lingkungan yang kondusif untuk pembelajaran siswa. Beragam kegiatan akademik dan non akademik yang berfungsi mengembangkan potensi peserta didik. Tumbuhnya karakter utama yang dibutuhkan untuk menciptakan pergaulan yang harmonis dan persaudaraan (ukhuwah) antar peserta didik. Kata Kunci: peran guru PAI, CERIA (cerdas, energik, religius, ilmiah, amaliyah), konsep implementasi